ASCIA guidelines for prevention of anaphylaxis in schools, pre‐schools and childcare: 2015 update. (October 2015) - Vale, Sandra; Smith, Jill; Said, Maria; Mullins, Raymond James; Loh, Richard
Abstract The aim of these guidelines is to assist staff in school and childcare settings to plan and implement appropriate risk minimisation strategies, taking into consideration the needs of the allergic child, the likely effectiveness of measures and the practicality of implementation. Although these guidelines include risk minimisation strategies for allergic reactions to insect stings or bites, latex and medication, the major focus relates to food allergy. This is due to the higher relative prevalence of food allergy in childhood (compared with other allergic triggers) and the higher likelihood of accidental exposure in these settings. Care of the allergic child in the school, pre‐school or childcare settings requires accurate information obtained from parents and carers, staff training in the recognition and management of acute allergic reactions, planning for unexpected reactions (including in those not previously identified as being at risk), age appropriate education of children with severe allergies and their peers, and implementation of practical strategies to reduce the risk of accidental exposure to known allergic triggers. Strategy development also needs to take into account local or regional established legislative or procedural guidelines and the possibility that the first episode of anaphylaxis may occur outside the home. Food bans are not recommended as the primary risk minimisation strategy due to difficulties in implementation and lack of proven effectiveness.